Excited-State Proton Transfer for Biomarker Detection - Debosreeta Bose; Agnishwar Girigoswami (Photochem)
Biomarker detection is imperative in the realms of modern medicine, biology, and environmental science, owing to the numerous avenues for its application. The recent scientific upsurge in the development of molecules, materials, and mechanisms for such scientific development has garnered considerable attention among scientists. In this connection, excited-state intramolecular proton transfer (ESIPT) properties of photoluminescent compounds provide considerable insights into the designing, development, and detection of biomarkers. ESIPT molecules significantly show a Stokes-shifted emission due to their sensitive nature and unique photophysical properties. Leveraging this photophysical property and tunable nature, several fluorescent probes of this genre can be designed and synthesized for a plethora of application spheres. Schiff bases encompass one such category of functional molecules displaying ESIPT properties, which can be mitigated by adding several other functionalities and desired optical characteristics. The current review article spans the basics of ESIPT properties of certain photoluminescent molecules and also envisages biosensing applications of recently developed imine–functionalized Schiff base molecules with such properties as the prima-foci, along with other applications.